Realidade interacionista da comunicação na gerência em enfermagem: significados, ações e mudanças - Lopes Neto, David (2002)
The purpose of this investigation was to analyse the ineanings, the meaningful actions and the clianges that happen in the management communication in nursing, bascd in the intetactive symbolic perspective by ineans of a abstraction of the reality of nurses who inanage the Services of nursing a hospital unit, in the city of Manaus-Amazonas, North of Brazil, from Juuc 15th 2000 to January 15ül of 2001. The informers ofthe study completed a sample of 30 nurses who included themselves in the selection criteria and ethical aspects. The techniques of free observation and semi-struetured interview with speeches recorder in tapes were used. The information was organized in a text editor, passing by a detailed exam through the tecliniquc of content analysis. The result were taken from the interviews and the observations of the researcher, putting together a group of four great thematies: management communication, meaningful actions, clianges and tacti le-visual field. The meaning of the management communication in nursing express that this kind of communication occurs through sharcd creation of meaningful symbols coming from interactive actions of managers and subordinates. Concerning the meaningful actions, tliey are symbols with different meaning, constructed by communication and interaction of nurse-managers with the other peoplc, from which lhe more evidenced were the care management, the managing functions, and interpessoal relationship. For these informeis, the clianges bccamc possiblc through the interpretative process of cach people involved in the managing communication, as each change was considered a real fact that makes part of the nursing routine. It was realized in the tactile-visual field that the nature of the communication objects exist for the nurses as produets of symbolic interaction with the managing work of nursing and hospital as a whole. From these rsults, it is cstablished the thesis that the effective communication in the managing in nursing occurs through the partaking of meaningful symbols constructed by maens of interaction due to the cominunicative process in the missionary work of nursing the human care.